Localizing the SDGs in England: Challenges and Value Propositions for Local Government - Perry, Beth; Diprose, Kristina; Taylor Buck, Nick; Simon, David (Frontiers in Sustainable Cities, 2021)
The United Nations' Development Goals (SDGs) have been criticized but are nonetheless seen by many as an important, if imperfect, international effort to address climate and environmental change, resource depletion and the unsustainability of contemporary life. Many of the Goals need to be implemented at the local level, yet sub-national governments have not been granted any enhanced status at the UN to facilitate this process. As a result, the role and effectiveness of local governments in localizing the SDGs is dependent on multi-level arrangements within respective national contexts. In this paper we present findings on the challenges facing local authorities in England, namely co-dependent ambivalence, partial holism and narrow practices of knowledge governance. We draw on work carried out collaboratively with local authorities and other stakeholders in Greater Manchester and Sheffield, and a UK-wide national workshop. These challenges explain the relatively low uptake and engagement with the SDGs in the context of wider political and economic concerns compared with international comparator cities. Against this background our research found that making the Goals real, relevant, relatable and relational offered a tactical route to localization for English local government.